(untitled) (Práxis Educativa, 2024)
Purpose: The purpose of this article is to explore the interrelationship between research ethics and research integrity with a focus on the primary forms of research misconduct, including plagiarism, fabrication, and falsification. It also details the main factors for their occurrence, and the possible ways for mitigating their use among scholars. Methods: The method employed a detailed examination of the main ethical dilemmas, as delineated in literature, as well as the factors leading to these ethical breaches and the strategies to mitigate them. Further, the teaching experiences of the primary author are reflected in the development of the model. Results: The results of this article are represented in a model illustrating the interrelationship between research ethics and research integrity. Further, a significant aspect of our article is the identification of novel forms of research misconduct concerning the use of irrelevant or forced citations or references. Conclusion: In conclusion, the article highlights the substantial positive effects that adherence to research ethics and integrity have on the academic well-being of scholars. Keywords: Research ethics. Research integrity. Research misconduct. Plagiarism. Fabrication.